Elusive Dehydroalanine Derivatives with Enhanced Reactivity. (1st April 2019) - Aydillo, Carlos; Mazo, Nuria; Navo, Claudio D.; Jiménez‐Osés, Gonzalo
Abstract: For the first time, a simple methodology for the chemical synthesis and use of highly reactive 4‐methylenoxazol‐5(4 H )‐ones from serine is presented. These dehydroalanine derivatives, which resemble the natural 4‐methylidenimidazole‐5‐one (MIO) cofactor present in lyases and aminomutases, undergo rapid reaction with carbon nucleophiles such as silyl enol ethers, as well as cycloaddition reactions with diazo compounds and reactive dienes, under very mild conditions and without any need for metal catalysts or ring‐strain activation, offering potential for bioconjugation. Abstract : Site‐selective bioconjugation and post‐translational modification of proteins under physiological conditions : A highly reactive and elusive dehydroalanine scaffold has been prepared for the first time. It reacted quickly in situ with a variety of reagents without any need for extra activation, thus paving the way for bioconjugation applications.